Dehydrogenase enzyme activity and lead (Pb) availability due to the application of biochar and Bacillus sp. in heavy metal-contaminated soil - Solekhah, Bella Agit; Priyadarshini, Rossyda; Maroeto, Maroeto (Journal of Degraded and Mining Lands Management, 2026)
The increase in industrial productivity has raised global concerns about heavy metal pollution in soil. Heavy metals pose a major obstacle to natural degradation processes, potentially disrupting the life of soil microorganisms and affecting the enzymes they produce. Intracellular dehydrogenases are more sensitive to contaminants than extracellular enzymes, making them highly effective indicators of heavy metal pollution in soil. This study aimed to evaluate soil dehydrogenase activity and lead (Pb) availability following the application of biochar and Bacillus sp. to heavy metal-contaminated soil. The experimental design used a completely randomized factorial design with two factors. The first factor was the form of giving rice husk biochar (D) with four dose levels: 0 t/ha (D0), 20 t/ha (D1), 40 t/ha (D2), and 60 t/ha (D3). The second factor was the application of Bacillus sp. bacteria (B), with doses of 0 mL/kg soil (B0) and 25 mL/kg soil (B1). The results of this study showed that the combination of rice husk biochar and Bacillus sp. significantly increased dehydrogenase enzyme activity. The highest increase was observed in the sixth week of incubation with D3B1 treatment (biochar at 60 t/ha and Bacillus sp. at 25 mL/kg soil), yielding a value of 2,465.53 TPF/g. In addition, the treatment significantly reduced lead availability, with the lowest value being 1.26 ppm.